The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1515/hf.2011.117
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemistry, color, dimensional stability and fungal resistance of Pinus radiata D. Don wood with oil heat-treatment

Abstract: Pinus radiata wood specimens were heat-treated at 160-2108C in linseed oil and the effects of treatment on chemical composition, color, dimensional stability, and fungal resistance were examined. The degradation of hemicelluloses was the most remarkable feature, which is the principal reason for alterations in wood properties. Removal or migration of extractives, oil uptake and the accumulation of oil on the wood surface were observed. The color of heattreated wood became more uniform and darker, and its dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 48 publications
5
94
0
12
Order By: Relevance
“…Heat-treated wood possesses novel properties, such as improved decay resistance, higher dimensional stability, aesthetic coloration, and photo-degradation (Dubey et al 2012;Persze and Tolvaj 2012;Bal and Bektaş 2013;Bekhta et al 2014;Aytin and Korkut 2015). However, adverse influences on mechanical characteristics, like impact strength, compression strength, and shear strength, restrict the heat-treated wood from being used in structural applications (Kasemsiri et al 2012;Bakar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Heat-treated wood possesses novel properties, such as improved decay resistance, higher dimensional stability, aesthetic coloration, and photo-degradation (Dubey et al 2012;Persze and Tolvaj 2012;Bal and Bektaş 2013;Bekhta et al 2014;Aytin and Korkut 2015). However, adverse influences on mechanical characteristics, like impact strength, compression strength, and shear strength, restrict the heat-treated wood from being used in structural applications (Kasemsiri et al 2012;Bakar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Important changes occurred at 2928, 2857, 1738, and 1373 cm -1 , and the region 1300 to 1193 cm -1 , which are indicative of the grafting of new functional groups to the wood (Chang and Chang 2001;Pandey and Vuorinen 2008;Pandey et al 2010;Dubey et al 2012). All the absorption bands increased significantly after modification with ELO.…”
Section: Ftir Spectroscopymentioning
confidence: 93%
“…The decrease in hemicellulose-a highly hydrophilic polymer-reduces the free hydroxyl groups. Because the transformation of carbohydrates blocks fungi growth and reproduction (Dubey et al 2012), heat-modified wood has better dimensional stability and decay resistance.…”
Section: Chemical Changes In Main Wood Componentsmentioning
confidence: 99%
“…2). Boonstra and Tjeerdsma (2006), Kocaefe et al (2008), and Dubey et al (2012) found that the absorption intensity at 1740 cm -1 decreased during the heat treatment, demonstrating that hemicellulose is not stable and is easily degraded by a high temperature treatment. In contrast, this study revealed that the peak areas at 1732 cm -1 increased with rising temperature, especially at 220 °C, and did not decrease (Fig.…”
Section: Ftir Analysis Of the Whole Wood Of Each Specimenmentioning
confidence: 99%
See 1 more Smart Citation